PENGEMBANGAN SISTEM INFORMASI PENJUALAN SEPATU PADA TOKO ANUGERAH JAYA - Nur Sucahyo; Riza Syahrial (Institut Teknologi dan Bisnis (ITB) Swadharma, 2021)
This study aims to analyze and develop an Anugerah Jaya store sales information system using the PIECES method. The problem faced at this time is that the sales system that is running is still manual, starting from the sales transaction process, the income calculation process, data collection on goods prices and inventory data are also still calculated by manual calculations that are only written on paper or books. This makes the quality of the information obtained is not optimal, less efficient and of course the possibility of misinformation is quite large. The research method used is a field study with data collection conducted through interviews and direct observation of the sales process. The results of the study based on the PIECES parameter analysis found several shortcomings in the sales process including the slow processing of data and the provision of reports. To overcome the existing problems, a new web-based system proposal was designed to overcome the current problems